See attached picture for solution:
The cost of each stone sphere is $ 36.81
<em><u>Solution:</u></em>
Given that,
An architect plans to buy 5 stone spheres and 3 stone cylinders
For the same amount, she can buy 2 stone spheres and 6 stone cylinders
Let "x" be that same amount
Let "a" be the cost of each stone sphere
Cost of each stone cylinder = $ 36.81
Therefore,
x = 5 stone spheres and 3 stone cylinders
x = 5a + 3(36.81)
Similarly,
x = 2 stone spheres and 6 stone cylinders
x = 2a + 6(36.81)
Equate both,
![5a + 3(36.81) = 2a + 6(36.81)\\\\5a + 110.43 = 2a + 220.86\\\\5a - 2a = 220.86 - 110.43\\\\3a = 110.43\\\\a = 36.81](https://tex.z-dn.net/?f=5a%20%2B%203%2836.81%29%20%3D%202a%20%2B%206%2836.81%29%5C%5C%5C%5C5a%20%2B%20110.43%20%3D%202a%20%2B%20220.86%5C%5C%5C%5C5a%20-%202a%20%3D%20220.86%20-%20110.43%5C%5C%5C%5C3a%20%3D%20110.43%5C%5C%5C%5Ca%20%3D%2036.81)
Thus cost of each stone sphere is $ 36.81
For this case we must write in algebraic symbology the expression described above:
We have an equation, then:
- x squared plus y squared:
![x ^ 2 + y ^ 2](https://tex.z-dn.net/?f=x%20%5E%202%20%2B%20y%20%5E%202)
- minus 2x plus 7y plus 1:
![-2x + 7y + 1](https://tex.z-dn.net/?f=-2x%20%2B%207y%20%2B%201)
- equals zero:
![= 0](https://tex.z-dn.net/?f=%3D%200)
We construct the equation:
![x ^ 2 + y ^ 2-2x + 7y + 1 = 0](https://tex.z-dn.net/?f=x%20%5E%202%20%2B%20y%20%5E%202-2x%20%2B%207y%20%2B%201%20%3D%200)
Answer:
![x ^ 2 + y ^ 2-2x + 7y + 1 = 0](https://tex.z-dn.net/?f=x%20%5E%202%20%2B%20y%20%5E%202-2x%20%2B%207y%20%2B%201%20%3D%200)
The answer is c, -1 or -7
Hope this helped :)
3x - 2 = 7
3x = 7 + 2
3x = 9 (divide both sides by 3 to get x)
3x/3 = 9/3
x = 3